Effect of loading rate on cohesive parameters of the adhesive Araldite 2015 - Erbayrak, Engin; Ozer, Halil (CARL HANSER VERLAG, 2020)
This study addresses the effect of loading rates on cohesive parameters and microstructural composition of the Araldite 2015 adhesive. Double Cantilever Beam (DCB) samples were tested under the loading rates of 1, 5, 10, 20, 100 and 200 mm x min(-1). The Park-Paulinho-Roeser model (PPR model) was used to get cohesive parameters. In modelling of the softening behavior, inverse analyses were performed using the date obtained from the PPR softening curves. It was seen that the fracture energy and cohesive parameters are decreasing with increasing the loading rate. However, there seems to be a transition region where the fracture energy nearly remains constant. Microstructural analyses were implemented in order to study the effects of the loading rates on the characteristics of the fracture surfaces. It was concluded that the loading rates greatly influence the distribution of micro-voids in the epoxy matrix. Moreover, the presence of voids in epoxy matrix improved the plastic deformation around the crack tip and increased the fracture toughness.
Keywords: Loading rate; fracture energy; PPR model; Araldite 2015; microstructural analyses; I FRACTURE-BEHAVIOR; MODE; TEMPERATURE; Materials Science